PENGARUH MANAJEMEN WAKTU SISWA TERHADAP PRESTASI BELAJAR EKONOMI SISWA KELAS XI IPS SMAN 2 SUNGAI RAYA KABUPATEN KUBU RAYA - Tomas, Tomas; Matsum, Junaidi H.; Witarsa, Witarsa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
this thesis is entitled student time management on economic learning achievement of class XI IPS student of SMAN 2 Sungai Raya,Kubu Raya Regency. The sub problem s are (1) how is the time management of class XI IPS student SMAN 2 Sungai Raya?; (2) how is the learning achievement of class XI IPS student SMAN 2 Sungai Raya?; (3) it there any influence of time management on learning achievement of class XI IPS SMAN 2 Sungai Raya? The research approach used is quantitative approach in the form of correlation. Data collection techniques used indirect communication techniques. The results showed (1)that time management of class XI IPS student of SMAN 2 Sungai Raya was categoriez as high;(2) that the learning achievement of student class XI IPS SMAN 2 Sungai Raya students was said to be good where 74 student or 87,06% got good grades and 11 student or 12,94%get a bad score;(3) student time management has an effect on student achievement in class XI IPS SMAN 2 Sungai Raya